The phenomenon of stigmatization in the real estate market - Tomasik, Klaudia (Ekonomia i Prawo. Economics and Law, 2024)
Motivation: The following article covers the entire path of stigmatization, from that which directly affects a person to special cases of real estate stigmatization. Market participants have created many types of stigmatization that discredit a property. These range from the more abstract ones (e.g., paranormal phenomena taking place on a property or superstition) to the more serious ones (e.g., a restricted use area). The following article focuses on properties located in restricted use areas and the impact of this factor on property values. It analyzes court rulings by Polish courts on compensation in connection with the decrease in the value of real estate due to the establishment of a restricted use area. Aim: The main goal of the article is to identify the phenomenon of stigmatization in the real estate market, while the specific goal is to identify the phenomenon of stigmatization of real estate in restricted use areas around airports. Results: One of the main reasons why stigmatization occurs in the real estate market is ignorance and people’s fear of what they don’t know. The most common objects of stigmatization are restricted use areas around airports. However, in the court rulings described in the article, there is no consensus on whether stigmatization of real estate in itself affects the value of real estate.